Innovative pedagogical strategies for deepening knowledge of inorganic synthesis in the system of continuous vocational education - Kochubei, Olena (Educological discourse, 2026)
The article investigates the problem of methodological support for teaching the discipline "Inorganic Synthesis" in the system of continuous professional education of future chemistry teachers. The relevance is due to the contradiction between the growing requirements for the subject and research competence of chemistry teachers and the insufficient methodological development of approaches to teaching the specified discipline in the conditions of digitalization of the educational process. The purpose of the article is the theoretical substantiation and systematization of pedagogical strategies, the application of which forms in applicants the ability to plan and analyze synthetic processes, interpret the structural and thermal properties of inorganic compounds, and also develops critical thinking and readiness for innovative pedagogical activity. The methodology combines theoretical analysis of domestic and foreign scientific and pedagogical sources (Scopus, Web of Science, ERIC), comparative and pedagogical analysis of practices of continuous chemical education of different countries and content analysis of curricula and digital platforms. Three key strategic directions are identified: integration of scientific content in coordination chemistry as a basis for case methodology and problem-based tasks; use of digital tools - virtual laboratories (Labster), simulation environments (PhET) - for practicing synthetic procedures and visualizing reaction mechanisms; use of project and blended learning to form research skills and pedagogical reflection. Methodological recommendations are proposed for updating the content and forms of the course. It is substantiated that the effectiveness of each strategy is determined by its subject-specific binding to the course objectives: understanding the mechanisms of coordination compound formation, planning synthetic routes, safe implementation of laboratory practice. Prospects for further research are seen in empirical verification of strategies based on measuring subject learning outcomes and developing adaptive digital courses.